Implementation of Al-Qur'an Science Training in improving Understanding and practice of Al-Qur'an values in MA Al-Amiriyyah Blokagung - Nur Aziza Turrohmah; Dena Izzatul Ulya (CV. Kalimasada Group, 2025)
This study aims to describe the implementation of the Qur'anic Studies Training Program in enhancing the understanding and practice of Qur'anic values at MA Al-Amiriyyah Blokagung. The background of this research is based on the importance of comprehensive religious development among students so that Qur'anic values are not only understood theoretically but also manifested in daily behavior. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. The findings indicate that the Qur'anic training program at this madrasah is carried out systematically through activities such as memorization (tahfidz), thematic interpretation (tafsir), Qur'anic character development (adab Qur’ani), and value-based practice in students’ daily lives. The program has a positive impact on students’ understanding of the content and meaning of the Qur'an and fosters behavioral changes reflecting Islamic values such as honesty, discipline, and responsibility. This study contributes to the development of a Qur'an-based educational model that can be adapted by other Islamic educational institutions to strengthen students’ character in facing the challenges of the modern era.